New Characterization of Topological Transitivity - Abdul Hussein, Hussein (Iraqi Journal of Science, 2024)
Letbe a dynamical system,is said to be topological transitive if for every pair of non-empty open set, there existssuch that. We introduce and investigate a new definition of topological transitive by using the nation N-open subset and we called N-transitive and prove the equivalent definitions of this new definition.